Different ways to skin a cat? The Balmoral Tanks information exchange appeal. Issue 2 (July 2019) - Kar, Nicole; Mitchell, Anna
Abstract : This article analyzes the Court of Appeal's judgment in the Balmoral Tanks information exchange case, upholding the Competition and Markets Authority's decision to fine Balmoral Tanks for the exchange of competitively sensitive information at a single meeting even though Balmoral Tanks was not part of a wider cartel. This judgment demonstrates the strict enforcement of competition law to information exchanges and the CMA's unusual approach adopting two separate infringement decisions – one relating to the main cartel and a separate decision relating to the information exchange – even though the participants to the cartel were also involved in the information exchange.